Flouting the Gricean Maxims in The Wild Robot (2024): A Pragmatic Analysis of Conversational Implicature in Animated Film Dialogue - Muhammad Ihsan Padila; Nazwa Yuki Nabila; Aidil Syahputra (Indo Publishing, 2026)
This study examines the flouting of Gricean conversational maxims in the animated film The Wild Robot (2024) and the conversational implicatures generated through such flouting. Grounded in Grice’s (1975) Cooperative Principle and its four maxims of Quality, Quantity, Relation, and Manner, the study adopts a descriptive qualitative research design to analyze dialogue exchanges among the film’s characters, particularly Roz, Fink, Brightbill, Thorn, and Vontra. Dialogue instances were identified, screened, and verified against the screenplay of The Wild Robot (2024) to ensure contextual accuracy, resulting in seventeen retained instances of maxim flouting. The findings indicate that the Maxim of Quality was flouted most frequently, accounting for nine instances (52.94%), followed by Relation with six instances (35.29%) and Quantity with two instances (11.76%). No instance of Manner flouting satisfied the inclusion criteria, a result treated as a legitimate descriptive finding rather than a shortcoming to be corrected. The flouted maxims were found to generate implicatures associated with sarcasm and irony, indirect emotional disclosure, redirection of sensitive questions, concealment of uncomfortable information, and protective concealment of danger. These findings are discussed in relation to previous Gricean studies of film dialogue, including analyses of Conclave (2024), Inside Out 2, and Thor: Ragnarok, situating The Wild Robot within existing pragmatic scholarship while addressing a specific gap in the literature: although the film has previously been examined through Systemic Functional Linguistics, its Gricean pragmatic dimension has received limited scholarly attention.